Screening Tea Cultivars for Novel Climates: Plant Growth and Leaf Quality of Camellia sinensis Cultivars Grown in Mississippi, United States - Zhang, Qianwen; Li, Tongyin; Wang, Qiushuang; LeCompte, Judson; Harkess, Richard L.; Bi, Guihong (Frontiers in Plant Science, 2020)
The United States (U.S.) consumed over 80 billion servings of tea, approximately 3.8 billion gallons, in the year of 2018. With the vast majority of tea demand being met by importation, the U.S. became the third largest tea importer worldwide after Russia and Pakistan. As demand for domestically produced tea increases and growers expressing increasing interest in growing and producing tea, tea production became an emerging industry in the U.S. Compared to major tea producing countries with centuries of growing history, tea production in the U.S. is limited and requires research support in many aspect of tea production including selecting suitable cultivars adapted to local climatic conditions. This study evaluated nine tea cultivars, including ‘BL1’, ‘BL2’, ‘Black Sea’, ‘Christine’s Choice’, ‘Dave’s Fave’, ‘Large Leaf’, ‘Small Leaf’, ‘Sochi’, and ‘var. assamica’, for plant growth, leaf morphological characteristics, cold tolerance, and leaf biochemical compositions when grown in Mississippi U.S. with a subtropical climate. The nine tested cultivars had varying plant growth indices (PGI) and varying degrees of cold tolerance to freezing temperatures in winter, but resumed healthy growth the following spring. ‘BL2’ showed the highest PGI of 104.53 cm by Feb. 2019, which might be helpful toward suppressing weed and early establishment of tea plantation. The nine cultivars also showed varying leaf characteristics in terms of leaf length, width, area, fresh and dry weights, and new shoot weight. There existed a diversity in leaf biochemical composition including soluble solids, carbohydrates, total polyphenols (TP), free amino acids (AA), L-theanine and caffeine among the nine cultivars and among different harvesting seasons of spring, summer, and fall within a certain cultivar. The nine cultivars in this study generally grow well in local environment. All tea samples collected from nine cultivars and three seasons were considered suitable for green tea processing with low TP/AA ratios ranging from 1.72 to 3.71 in this study.